PERENCANAAN CHECK DAM GALEH KABUPATEN TEMANGGUNG - Andin Cipto Nugroho; Hasan Mudhofar; Sri Sangkawati; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Galeh river is one of rivers which are on the slopes sindoro ( 3153 mdpl ). Galeh river in length a major river more or less 18,3 km with broad das 41,05 km². The distance landscapes of the river galeh is ± 35 m, and slope the river that is 12,35 %. With a baseline a river that relatively precipitous, so the flow of high speed would be easy gradually crushed, especially on the basis, the river wall, who has resulted in the erosion and sedimentation. To reduce the potential this danger, attempts to prevention of building construction control sediment (Check Dam). From the data hydrology in the form of rainfall daily, DAS map, topographical maps and map geometry the discharge flood get the target 283,044 m3/seconds. Data hydrological and reference is to be cultivated as the basis for planning main dam, sub dam, apron, and support buildings other, obtained the results of the total in the form of high Main Dam 3,55 meters as much as, high total Sub Dam 2.2 meters, long an apron of about 20 m and volume tampungan 5.478,27 m³ as much as, with a total cost amounting to Rp 2.362.300.000,-. Check Dam development will be more optimal if accompanied by a system of the observance of which either by other relevant offices prosentase it is expected that the affected areas the flow of sedimentation can be reduced significantly..